Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Sabun Cuci Piring di Dusun IV Desa Selemak - Yummy Jumiati Marsa; Salsabila Febriani; Aninda Nurul Rahmayanti; Syahirah Rizky; Maharani Adawiyah (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
In an effort to help advance the underdeveloped villages in Selemak Village, especially in hamlet IV, service activities in the form of easy and innovative training have been carried out. The training conducted by Selemak Village, especially in Hamlet IV, aims to empower housewives to be creative in making a product. One of these a products is to make dish soap that is fast and marketable so that it helps the family's economy. The target to be achieved is for housewives to become more independent in facing an increasingly advanced economy. However, there are still constrained factors in making dish soap because the ingredients used are chemical which are rarely sold in the market, resulting in a business opportunity to make dish soap an obstacle. Therefore, the training team tried to find the nearest shop to help housewives buy the ingredients for making dish soap. So the first method is field observation, which is identifying problems that occur and finding solutions, secondly, socialization is to provide education on how to make it and how to market it, the third practice is a video appearance on how to make dish soap that has been made by the Real Work Lecture team. KKN) group 67. This is so that the process of making dish soap for housewives can provide benefits for the economy and can be used for daily needs. Keywords: empowerment, training, housewife, dish soap